Tabebuia rosea: uma revisão sistemática de suas propriedades farmacológicas e uso na medicina tradicional - Barreto, Rosalin Santana (2022)
Tabebuia rosea is a plant native to southern Mexico, Central America and part of Latin America, and is traditionally used to treat snake bites, ulcers, cancer, diabetes and skin conditions. The extracts obtained from different parts of this plant have shown different pharmacological activities in the literature. This systematic review aimed to describe and structure the main pharmacological actions and their use in traditional medicine by searching the PubMed, Scopus, Science Direct, Scielo and Lilacs databases, using the keywords 'Tabebuia'; ‘Plant Extracts’ and ‘Traditional Medicine. A total of 234 scientific documents were founded, of which 9 articles met the established inclusion criteria. The results showed that extracts obtained from T. rosea showed pharmacological activities such as anti-hemorrhagic, antiophidic, anxiolytic and antiulcer. In addition, the presence of anti-inflammatory activity by inhibition of nitric oxide, prostaglandin 2 and TNF-α was evidenced, and a potent antioxidant activity similar to quercetin, associated with a decrease in the levels of Nrf2 (nuclear erythroid factor 2) in the cytoplasm and an increase in the nucleus, as well as an increase in the expression of NQO1 (NADPH quinone oxidoreductase). Antiproliferative activity was also evidenced in different tumor cell lines and absence of antifungal activity. The traditional use, in addition to those already known, was evidenced in gynecological, respiratory, liver dysfunctions and epileptic seizures. The recurrent use of T. rosea in research in Latin American countries gives credit to the importance of the studies. Therefore, the continuity of research into its properties, as well as the discovery of new activities, is of paramount importance as an innovative strategy in the prevention and treatment of various diseases.